Pengembangan Instrumen Penilaian Civic skills dan Action citizen Pendidikan Kewarganegaraan pada Materi Keberagaman Indonesia bagi Peserta Didik SMP berbasis Google Form - Irliandi, Ina Aina; Tri Sumniar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Assessment practices in Civic Education at the junior high school level are still predominantly focused on cognitive aspects, which limits their ability to measure students’ Civic skills and action citizen comprehensively, particularly in the topic of Indonesian Diversity. This condition highlights the need for the development of assessment instruments that can accommodate students’ Civic skills and active participation. This study aims to develop a Google Form–based assessment instrument for Civic skills and action citizen that is valid, reliable, and practical foruse in Civic Education learning. This study employed a Research and Development approach by adapting Mardapi’s instrument development model, which was simplified into nine stages. The research subjects included junior high school students and Civic Education teachers. Data were collected through expert validation, questionnaires, and instrument trials. The results indicate that the developed assessment instrument meets the criteria of validity and reliability and demonstrates a very high level of practicality. Therefore, the Google Form–based assessment instrument for Civic skills and action citizen is feasible to be used as an alternative form of authentic assessment in Civic Education learning, particularly for the topic of Indonesian Diversity at the junior high school level. This study recommends that the developed instrument be implemented more widely, supported by training for Civic Education teachers on digital-based authentic assessment. Furthermore, future development is suggested to expand the instrument so that it can be applied to other topics in Civic Education.